Urinary mycoestrogens and gestational weight gain in the UPSIDE pregnancy cohort - Carolyn W. Kinkade; Zorimar Rivera-Núñez; Anita Brinker; Brian Buckley; Olivia Waysack; Amber Kautz; Ying Meng; Pamela Ohman Strickland; Robert Block; Susan W. Groth; Thomas G. O’Connor; Lauren M. Aleksunes; et al. (Environmental Health, 2024)
Abstract Background Zearalenone (ZEN), a secondary metabolite of Fusarium fungi, is one of the most common mycotoxins in global food supplies such as cereal grains and processed food. ZEN and its metabolites are commonly referred to as mycoestrogens, due to their ability to directly bind nuclear estrogen receptors α (ER-α) and β (ER-β). Zeranol, a synthetic mycoestrogen, is administered to U.S. cattle as a growth promoter. Despite widespread human exposure and ample evidence of adverse reproductive impacts in vitro and in vivo, there has been little epidemiological research on the health impacts of ZEN exposure during pregnancy. The objective of our study was to examine associations between ZEN and gestational weight gain (GWG). Methods Urine samples were collected in each trimester from pregnant participants in the UPSIDE cohort (n = 286, Rochester, NY, USA). High performance liquid chromatography and high-resolution tandem mass spectrometry were used to quantify concentrations of ZEN as well as ∑mycoestrogens (composite sum of ZEN metabolites; ng/ml). Maternal weights at clinical visits were abstracted from medical records. We fitted longitudinal models of specific-gravity adjusted, log-transformed ZEN and ∑mycoestrogens in relation to total GWG (kilograms) and GWG rate (kilograms/week). We additionally examined risk of excessive GWG (in relation to Institute of Medicine guidelines) and considered effect modification by fetal sex. Results ZEN and ∑mycoestrogens were detected in > 93% and > 95% of samples, respectively. Mycoestrogen concentrations were positively associated with total GWG (ZEN β:0.50 kg; 95%CI: 0.13, 0.87) and GWG rate (ZEN β:0.20 kg/week; 95%CI: 0.01, 0.03). Associations tended to be stronger among participants carrying male (versus female) fetuses and results were robust to adjustment for diet. Conclusions Mycoestrogen exposure during pregnancy may contribute to greater GWG. Future research is needed to understand potential influences on downstream maternal and offspring health.